2022
DOI: 10.1136/jnnp-2021-327376
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of validated Parkinson’s disease subtypes in the Oxford Discovery and Tracking Parkinson’s cohorts

Abstract: ObjectivesTo explore the genetics of four Parkinson’s disease (PD) subtypes that have been previously described in two large cohorts of patients with recently diagnosed PD. These subtypes came from a data-driven cluster analysis of phenotypic variables.MethodsWe looked at the frequency of genetic mutations in glucocerebrosidase (GBA) and leucine-rich repeat kinase 2 against our subtypes. Then we calculated Genetic Risk Scores (GRS) for PD, multiple system atrophy, progressive supranuclear palsy, Lewy body deme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…A potentially informative approach that leverages existing datasets is to explore differences in disease biology markers across clinically defined PD subtypes. An example is the effort to match significant differences in genetic, 56 pro‐inflammatory, 57 vascular and alpha‐synuclein markers found across four PD subtypes 58 with perturbed cellular phenotypes using iPSc‐generated models. If clinically defined PD subtypes match underlying biology, this could permit efficient clinical application of a more targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A potentially informative approach that leverages existing datasets is to explore differences in disease biology markers across clinically defined PD subtypes. An example is the effort to match significant differences in genetic, 56 pro‐inflammatory, 57 vascular and alpha‐synuclein markers found across four PD subtypes 58 with perturbed cellular phenotypes using iPSc‐generated models. If clinically defined PD subtypes match underlying biology, this could permit efficient clinical application of a more targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“… Liu et al (2021) , in a study of 3,821 patients, identified three novel loci associated with cognitive progression in PD, in addition to confirming associations with GBA1 and APOE. Tan et al (2022) , in an analysis of 11 cohorts from Europe and the Americas, including the PPMI, Tracking Parkinson’s, and Oxford Discovery cohorts ( Lawton et al, 2022 ), identified six novel loci associated with PD motor progression or mortality, and found that the E326K GBA1 variant was associated with increased mortality. Martínez Carrasco et al (2023) , in a GWAS meta-analysis, identified an association between axial motor progression and expression of ACP6 that suggests mitochondrial lipid homeostasis plays a role in motor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Patients of EOPD with SNCA mutations show asymmetric onset, good responsiveness for L-dopa in initial time, early motor complications, rapid progression and worse cognitive impairment (Trinh et al, 2018;Chen et al, 2020;Zhao et al, 2020). Potential explanations of subtype differences include different PD-associated protein dysfunctions (Quinn et al, 2020;Mencke et al, 2021;Menozzi and Schapira, 2021), different accumulation rates of pathogenic alpha-synuclein (Lawton et al, 2022), different trajectories of pathology progression (De Pablo-Fernández et al, 2019) or possibly even different compensatory capacities in the neural circuits (Palermo et al, 2020;Wang et al, 2022). Future studies should focus on understanding the underlying disease pathophysiology that drives these different clinical clusters in EOPD and their subsequent progression.…”
Section: Discussionmentioning
confidence: 99%